Sinomenine in Cardio-Cerebrovascular Diseases: Potential Therapeutic Effects and Pharmacological Evidences - Zhang, Meng-Wan; Wang, Xiao-Hui; Shi, Jing; Yu, Jian-Guang (Frontiers in Cardiovascular Medicine, 2021)
Cardio-cerebrovascular diseases, as a major cause of health loss all over the world, contribute to an important part of the global burden of disease. A large number of traditional Chinese medicines have been proved effective both clinically and in pharmacological investigations, with the acceleration of the modernization of Chinese medicine. Sinomenine is the main active constituent of sinomenium acutum and has been generally used in therapies of rheumatoid arthritis and neuralgia. Varieties of pharmacological effects of sinomenine in cardio-cerebrovascular system have been discovered recently, suggesting an inspiring application prospect of sinomenine in cardio-cerebrovascular diseases. Sinomenine may retard the progression of atherosclerosis by attenuating endothelial inflammation, regulating immune cells function, and inhibiting the proliferation of vascular smooth muscle cells. Sinomenine also alleviates chronic cardiac allograft rejection relying on its anti-inflammatory and anti-hyperplastic activities and suppresses autoimmune myocarditis by immunosuppression. Prevention of myocardial or cerebral ischemia-reperfusion injury by sinomenine is associated with its modulation of cardiomyocyte death, inflammation, calcium overload, and oxidative stress. The regulatory effects on vasodilation and electrophysiology make sinomenine a promising drug to treat hypertension and arrhythmia. Here, in this review, we will illustrate the pharmacological activities of sinomenine in cardio-cerebrovascular system and elaborate the underlying mechanisms, as well as give an overview of the potential therapeutic roles of sinomenine in cardio-cerebrovascular diseases, trying to provide clues and bases for its clinical usage.